Electroacupuncture attenuates working memory impairement after chronic stress exposure in rat - Selfi Handayani; Nanang Wiyono (JURNAL KEDOKTERAN DAN KESEHATAN, 2017)
Chronic stress (CS) exposure causes cytogenic and structural changes in the hipocampus which lead to cognitive impairment. Acupuncture has been shown to reduce cortisol secretion and protects hipocampus from stress-related damage. We hypothesize that acupunture can alleviate stress-induced working memory deficit.mthis study aimed to investigate whether electroacupuncture (EA) can improve memory in chronic stress model in rat. This was an experimental study with pretest and postest control group design. Rats were divided randomly into four groups: control group (C), CS group (T1), EA group (T2), and EA plus CS group (T3). Working memory was assessed using Eight-arm radial maze. A marked decrease in working memory was observed in the CS group demonstrated by more working memory correct errors (p=0.020) and incorrect errors (p=0.024) than control group. The CS plus EA rats made fewer working memory correct error (p=0.001) and incorrect error (p=0.000) compared to the CS only group. EA treatment in non-stressed rats did not significantly improve working memory compared to control. Chronic stress decreases working memory in rats. EA treatment at Baihui (DU 20) and Zusanli (ST 36) significantly attenuates stress induced working memory deficits in rats.